2011
DOI: 10.1136/bmjopen-2010-000021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of distant reiki on pain in women after elective Caesarean section: a double-blinded randomised controlled trial

Abstract: IntroductionApproximately 25% of all babies in North America are delivered via Caesarean section (C-section). Though a common surgical procedure, C-section recovery can be painful. Opioids, specifically codeine, are commonly used to ease pain; however, its active metabolite, morphine, passes into breast milk, and may produce unwanted side effects in neonates; therefore, alternatives to opioids are being sought. Reiki is an ancient Japanese form of healing where practitioners transfer healing energy through lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 40 publications
(27 reference statements)
0
46
0
4
Order By: Relevance
“…9,10 Moreover, these factors were in line with our aim in this systematic review, which was to evaluate perceived pain among women undergoing cesarean section. Moreover, both reiki and prayer meditation are non-invasive and non-pharmacological practices, and both of them can be considered to be spiritual interventions.…”
Section: Lilacsmentioning
confidence: 56%
See 3 more Smart Citations
“…9,10 Moreover, these factors were in line with our aim in this systematic review, which was to evaluate perceived pain among women undergoing cesarean section. Moreover, both reiki and prayer meditation are non-invasive and non-pharmacological practices, and both of them can be considered to be spiritual interventions.…”
Section: Lilacsmentioning
confidence: 56%
“…In the overall analysis with regard to systolic blood pressure, the results from two RCTs 9,10 showed that there was no statistically significant difference favoring reiki over the usual care: MD = -3.59; 95% CI: -6.79 to 0.39; P = 0.03; I 2 = 26%. Therefore, we also found no statistically significant difference favoring reiki over the usual care: MD = -1.71; 95% CI: -6.21 to 2.79; P = 0.25; I 2 = not applicable.…”
Section: Systolic Blood Pressurementioning
confidence: 94%
See 2 more Smart Citations
“…O Reiki é uma técnica de canalização de energia vital através de símbolos e sons sagrados, esta energia ainda não é qualificada pela física moderna, porém alguns autores relatam a existência de um biocampo, que seria o Campo de Energia (CE) intrínseco a todos os seres vivos, chamado também de campo quântico, clássico e não clássico (VANDERVAART et al, 2011).…”
Section: Introductionunclassified